Fur: A non-invasive approach to monitor metal exposure in bats. (March 2016) - Hernout, Béatrice V.; McClean, Colin J.; Arnold, Kathryn E.; Walls, Michael; Baxter, Malcolm; Boxall, Alistair B.A.
Abstract: This paper presents a novel assessment of the use of fur as a non-invasive proxy to biomonitor metal contamination in insectivorous bats. Concentrations of metals (cadmium, copper, lead and zinc) were measured using ICP-MS in tissues (kidneys, liver, stomach and stomach content, bones and fur) obtained from 193 Pipistrellus pipistrellus/pygmaeus bats. The bats were collected across a gradient of metal pollution in England and Wales. The utility of small samples of fur as an indicator of metal exposure from the environment was demonstrated with strong relationships obtained between the concentrations of non-essential metals in fur with concentrations in stomach content, kidneys, liver and bones. Stronger relationships were observed for non-essential metals than for essential metals. Fur analyses might therefore be a useful non-invasive proxy for understanding recent, as well as long term and chronic, metal exposure of live animals. The use of fur may provide valuable information on the level of endogenous metal exposure and contamination of bat populations and communities. Highlights: A unique monitoring dataset explores the utility of bat fur as a biomarker. Concentrations of metals in fur were correlated with concentrations in other tissues. Fur is a non-invasive proxy that can be used to monitor metal contamination in bats. Fur analyses can be used to understand recent, long term and chronic metal exposure.